O-005 Combination Therapy with Methotrexate Does Not Change Infliximab Pharmacokinetics in Children with Inflammatory Bowel Disease. (February 2017) - Shakhnovich, Valentina; Van Haandel, Leon; Becker, Mara; Funk, Ryan
Abstract : Background: There remains a question of equipoise regarding the use of anti-TNF-α agent (e.g., infliximab) monotherapy versus combination therapy with immunomodulators (e.g., methotrexate), for the treatment of pediatric Inflammatory Bowel Disease (IBD). The aim of this prospective cross-sectional study was to assess the impact of methotrexate (MTX) on infliximab (IFX) pharmacokinetics (i.e., serum trough levels) and infliximab antibody (anti-IFX) formation in children with IBD. Methods: Forty-one children with IBD (9–21 yr of age), receiving maintenance IFX infusions as part of their standard-of-medical-care, had serum IFX and anti-IFX concentrations assessed via an established NF-kB luciferase gene-reporter assay (ARUP Laboratories). Clinical and laboratory data were collected on all patients from a detailed review of their medical records. Children who had IFX dose or dose-interval adjustments during the previous 2 IFX infusions, or those who had received <14 weeks of IFX therapy, were excluded. For those children receiving concomitant therapy with MTX (n = 12) dose-for-weight-adjusted erythrocyte MTX concentrations were determined via validated HPLC-MS/MS methodology. After adjusting for dose-per-kg of IFX received, serum trough IFX and anti-IFX concentrations were compared via independent student t test in 29 children receiving IFX monotherapy versus 12 children receiving IFX combination therapy with MTX. Relationships between IFX exposure, MTX exposure, age, weight, and IFX dosing interval were explored via Spearman's correlation (rs ). All statistical analyses were performed using SPSS v23; α < 0.05. Results: Adjusted for mg/kg IFX dose, serum trough IFX concentrations were similar in children receiving IFX monotherapy (1.73 ± 1.58 μg/mL) versus combination therapy with MTX (1.64 ± 1.54 μg/mL); P = 0.5. Higher erythrocyte MTX concentrations were not associated with higher serum IFX trough levels (rs = −0.065; P = 0.69). Two out of 41 children (4.9%) had detectable anti-IFX concentrations, one receiving IFX monotherapy and one receiving IFX combination therapy. No statistical differences in baseline patient age, ESR, CRP or albumin were observed between children receiving IFX monotherapy and children receiving IFX combination therapy with MTX. Conclusions: In children receiving IFX maintenance therapy for the treatment of IBD, combination therapy of IFX with MTX did not appear to affect serum IFX trough levels or anti-IFX formation. Higher erythrocyte MTX concentrations did not correlate with higher serum IFX troughs, suggesting that the observed lack of MTX effect on IFX pharmacokinetics is not MTX dose-dependent. The prevalence of anti-IFX in our cohort of pediatric patients was low (4.9%) and similar in children receiving IFX monotherapy versus combination therapy with MTX, suggesting no pharmacokinetic advantage of combination therapy.